2023
DOI: 10.1111/jgs.18140
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation and 9‐year dementia risk in community‐dwelling Medicare beneficiaries in the United States

Abstract: Background Social isolation can influence whether older adults develop dementia. We examine the association between social isolation and incident dementia among older adults in a nationally representative sample of community dwelling older adults in the United States (U.S.). We also investigate whether this association varies by race and ethnicity. Methods Data (N = 5022) come from the National Health and Aging Trends Study, a longitudinal and nationally representative cohort of older adults in the U.S. A comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 39 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Social isolation is associated with negative health outcomes, especially for Black and Latino older adults. A new study from Johns Hopkins University found that social isolation increases the risk for developing dementia among older adults [ 11 ]. Among older adults, Black people, Latino people, and people with fewer years of education experience more loneliness, leading to higher levels of stress, poor cardiovascular health, depressive symptoms, and cognitive decline, among many other conditions [ 6 ].…”
Section: Social Determinants Of Health: Social Isolation and Caregivi...mentioning
confidence: 99%
“…Social isolation is associated with negative health outcomes, especially for Black and Latino older adults. A new study from Johns Hopkins University found that social isolation increases the risk for developing dementia among older adults [ 11 ]. Among older adults, Black people, Latino people, and people with fewer years of education experience more loneliness, leading to higher levels of stress, poor cardiovascular health, depressive symptoms, and cognitive decline, among many other conditions [ 6 ].…”
Section: Social Determinants Of Health: Social Isolation and Caregivi...mentioning
confidence: 99%
“…A review by Majoka and Schimming (2021) explored the literature connecting SDoH factors and ADRD risk and found that higher levels of SES (i.e., household income) were generally associated with reduced risk and longer time to ADRD diagnosis, and that racial discrimination can exacerbate disparities in ADRD risk. Although social isolation is known to increase dementia risk (Huang et al, 2023), social engagement is associated with greater gray matter microstructural integrity, reflecting better brain cellular health, in dementia-prone brain regions (Felix et al, 2021) among older adults.…”
Section: Sdoh and Adrd Riskmentioning
confidence: 99%
“…[1] Social isolation can lead to harmful health outcomes (e.g., dementia, depression, and lower quality of life) and can also limit access to health promoting resources (e.g., shared information, emotional support, physical assistance) potentially available through a social support network. [1][2][3][4] In the United States (U.S.), 24% of older adults are socially isolated. [5].…”
Section: Introductionmentioning
confidence: 99%